Imaginarios urbanos como esencia de proyectos en la formación de diseñadores industriales - Cardona, Félix Augusto; jorge.escobar@ucp.edu.co (Universidad Católica de Pereira, 2011)
The following article describes the academic exercise developed in the course of social design workshop of the industrial design career on sixth semester based on the conceptual approach of the social imagination from the urban issue to propose design products in a particular subject. For the purpose to sensitize the student in the social notion of design from a personal and autonomous perspective. It corresponding to an explicit, logical and consistent process from his own experience to create the design´s determinants for the development of a three-dimensional creation which might become a requirements product in the academic framework at this stage of his professional academic formation.